Real-world persistence and adherence to oral antimuscarinics and mirabegron in patients with overactive bladder (OAB): a systematic literature review. Issue 11 (21st November 2018) - Yeowell, Gillian; Smith, Philip; Nazir, Jameel; Hakimi, Zalmai; Siddiqui, Emad; Fatoye, Francis
Abstract : Purpose: To evaluate persistence and adherence of oral pharmacotherapy used in the treatment of overactive bladder (OAB) in a real-world setting. Materials and methods: Systematic literature searches of six electronic publication databases were performed to identify observational studies of patients with OAB treated with antimuscarinics and/or mirabegron. Studies obtaining persistence and adherence data from sources other than electronic prescription claims were excluded. Reference lists of identified studies and relevant systematic reviews were assessed to identify additional relevant studies. Results: The search identified 3897 studies, of which 30 were included. Overall, persistence ranged from 5% to 47%. In studies reporting data for antimuscarinics and mirabegron (n=3), 1-year persistence was 12%–25% and 32%–38%, respectively. Median time to discontinuation was <5 months for antimuscarinics (except one study (6.5 months)) and 5.6–7.4 months for mirabegron. The proportion of patients adherent at 1 year varied between 15% and 44%. In studies reporting adherence for antimuscarinics and mirabegron, adherence was higher with mirabegron (mean medication possession ratio (MPR): 0.59 vs 0.41–0.53; mean proportion of days covered: 0.66 vs 0.55; and median MPR: 0.65 vs 0.19–0.49). Reported determinants of persistence and adherence included female (sex), older age group, use of extended-release formulation and treatment experience. Conclusion: Most patients with OAB discontinued oral OAB pharmacotherapy and were non-adherent 1 year after treatment initiation. In general, mirabegron was associated with greater persistence and adherence compared with antimuscarinics. Combined with existing clinical trial evidence, this real-world review merits consideration of mirabegron for first-line pharmacological treatment among patients with OAB. PROSPERO registration number: CRD42017059894.